Abnormalities of Dopamine D3 Receptor Signaling in the Diseased Brain. (14th August 2017) - Prieto, G Aleph
Dopamine D3 receptors (D3 R) modulate neuronal activity in several brain regions including cortex, striatum, cerebellum, and hippocampus. A growing body of evidence suggests that aberrant D3 R signaling contributes to multiple brain diseases, such as Parkinson's disease, essential tremor, schizophrenia, and addiction. In line with these findings, D3 R has emerged as a potential target in the treatment of neurological disorders. However, the mechanisms underlying neuronal D3 R signaling are poorly understood, either in healthy or diseased brain. Here, I review the molecular mechanisms involved in D3 R signaling via monomeric D3 R and heteromeric receptor complexes (e.g., D3 R-D1 R, D3 R-D2 R, D3 R-A2a R, and D3 R-D3 nf). I focus on D3 R signaling pathways that, according to recent reports, contribute to pathological brain states. In particular, I describe evidence on both quantitative (e.g., increased number or affinity) and qualitative (e.g., switched signaling) changes in D3 R that has been associated with brain dysfunction. I conclude with a description of basic mechanisms that modulate D3 R signaling such as desensitization, as disruption of these mechanisms may underlie pathological changes in D3 R signaling. Because several lines of evidence support the idea that imbalances in D3 R signaling alter neural function, a better understanding of downstream D3 R pathways is likely to reveal novel therapeutic strategies toward dopamine-related brain disorders.